2020
DOI: 10.1155/2020/1484687
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Complaints in Two Large Tertiary University Teaching Hospital ENT Departments: A Two-Year Retrospective Review

Abstract: Introduction. Complaints relating to patient care are known to correlate with surgical complication rates and malpractice lawsuits. In a continually evolving health service and on-going financial pressures, identifying current complaint themes could drive future improvements in healthcare delivery. Objective. e aim of this paper is to review and analyse complaints received by the ENT department of two large teaching hospitals in London in order to determine current trends and mitigate future challenges. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 21 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…Patients felt abandoned when they were left alone in precarious situations (Andersson et al, 2015; Eriksson & Svedlund, 2007; Jangland et al, 2009; Ming et al, 2019), sometimes without the ability to contact health care professionals (Andersson et al, 2015; Eriksson & Svedlund, 2007). Incidents where patients experienced unnecessary pain because of rough treatment from health care professionals during procedures (Andersson et al, 2015; Bujoreanu et al, 2020; Eriksson & Svedlund, 2007; Giles et al, 2009; Wessel et al, 2009) or when pain medication was delayed (Bujoreanu et al, 2020; Eriksson & Svedlund, 2007; Wessel et al, 2009) or denied (Cowan & Wilson, 2007; Skär & Söderberg, 2012; Wofford et al, 2004) were also described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients felt abandoned when they were left alone in precarious situations (Andersson et al, 2015; Eriksson & Svedlund, 2007; Jangland et al, 2009; Ming et al, 2019), sometimes without the ability to contact health care professionals (Andersson et al, 2015; Eriksson & Svedlund, 2007). Incidents where patients experienced unnecessary pain because of rough treatment from health care professionals during procedures (Andersson et al, 2015; Bujoreanu et al, 2020; Eriksson & Svedlund, 2007; Giles et al, 2009; Wessel et al, 2009) or when pain medication was delayed (Bujoreanu et al, 2020; Eriksson & Svedlund, 2007; Wessel et al, 2009) or denied (Cowan & Wilson, 2007; Skär & Söderberg, 2012; Wofford et al, 2004) were also described.…”
Section: Resultsmentioning
confidence: 99%
“…Not even on Friday morning, 16th May, which was the day that mother died, were we told how serious the situation was and had been during the night and over the last few days. (Andersson et al, 2015, p. 381) Other patients said they received information that was difficult to understand (Hogg et al, 2018;Jangland et al, 2009;Ming et al, 2019;Olsson, 2016;Söderberg et al, 2012;Wofford et al, 2004), and were given no time to ask questions (Bujoreanu et al, 2020;Jangland et al, 2011;Kee et al, 2018;Olsson, 2016;Söderberg et al, 2012;Wessel et al, 2009).…”
Section: Ryynänen Andmentioning
confidence: 99%
“…Murphy et al (2009), in their study on the effect of nurse education on the care behavior of student nurses, found that there was a statistically significant decrease in caring behavior with the third‐year scores being less than the first year. Bujoreanu et al (2020) reported that nurses become reckless in certain situations and may change over time. In addition, caring behavior scores were found to be higher in nurse educators than clinical nurses (Loke et al, 2015; Tanyer & Gozutok‐Konuk, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Novelin and Kuntarti (2021) determined that peer care behavior practices led to an increased relationship between nursing internship students and patients. However, it is seen that clinical nurses do not practice their care behaviors in time (Bujoreanu et al, 2020). On the other hand, no study has been found about the mentors' instilling care behaviors for nurse students.…”
Section: Introductionmentioning
confidence: 99%
“…The Healthcare Complaints Analysis Tool (HCAT) ( 8 10 ) was developed to facilitate extraction of data from formal complaints, thereby enhancing organizational listening, analysis and aggregation of complaints data to improve service monitoring and institutional learning. However, HCAT has been predominantly applied in adult settings with less complex complaints ( 8 , 10 , 11 ). One recent study reviewed physician-related patient complaints in a Canadian specialist pediatric hospital and categorized them using HCAT ( 12 ).…”
Section: Introductionmentioning
confidence: 99%